Pemanfaatan Limbah Biji Alpukat Dan Kulit Kacang Tanah Sebagai Bahan Baku Plastik Ramah Lingkungan (Degradable) Dengan Penambahan Gliserol - Anggarayni, Titian Nicgia; , Dra. Aminah Asngad, M.Si (2017)
Plastic waste degradation needed long period of time, so that it caused increasingly accumulated plastic wastes. A way of reducing plastic wastes was the use of environmentally friendly plastic. Starch contained in avocado seed was main raw material of the environmentally friendly plastic. Addition of cellulose and glycerol in the making of environmentally friendly plastic can improve physical and mechanical characteristics of the plastic. Purpose of the research was to know tensile strength, breaking elongation and degradas of the environmentally friendly plastic. The research used full randomized design with two factors of, namely ratio of raw materials between avocado seed and peanut shell of 8.5g:1.5g, 9g:1g, 9.5g:0.5g and additions of glycerol were 6ml, 7ml, 8ml. Results of observation data was analyzed descriptive-qualitatively. Results of the research indicated that the strongest tensile strength, 1.86 N/mm2, was found with A2G3 treatment, longest breaking elongation, 65.33%, was found with A2G1 treatment. Result of the best degradability was found with addition of 8ml glycerol with residual reduction of 53.153%.